Assessment of the competitiveness and effectiveness of an open business model in the industry 4.0 environment - Sandra Grabowska; Sebastian Saniuk (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
With the changing conditions of business conduct, Industry 4.0 means a rapid development of new technologies, increased intensity of competition and evolving globalization, thus presenting enterprises with new challenges. There is a need to transform business models into open models that make extensive use of open innovations. A company's aspiration to achieve success on the market requires monitoring the degree of strategy implementation. The aim of this article is to present a tool for assessing the competitiveness and effectiveness of the business model of an enterprise in the Industry 4.0 era. The tool for assessing the business model is based on the balanced scorecard. It was constructed on the basis of literature and expert research. The article presents its practical application in an enterprise.
Keywords: 650; open business model; open innovations; Industry 4.0; balanced scorecard; competitiveness; efficiency